Anesthesia in the modern world of apps and technology: Implications and impact on wellness. Issue 1 (23rd November 2020) - Lo, Calvin; Yu, Julie; Görges, Matthias; Matava, Clyde
Summary: Recent decades have seen an unprecedented leap in digital innovation, with far‐reaching implications in healthcare. Anesthesiologists have historically championed the adoption of new technologies. However, the rapid evolution of these technologies has outpaced attempts at studying their potential impact on healthcare providers' well‐being. This document introduces several categories of workplace technologies commonly encountered by the anesthesiologist. We examine examples of novel technology and the impact of these digital interventions on the anesthesiologist's well‐being. We also review popular personalized technology aimed at improving wellness and the impact on well‐being examined. Finally, technology acceptance models are introduced to improve technology adoption, which, when appropriately applied, may minimize the negative impacts of technology on anesthesiologists' well‐being. Incorporating quantitative, serial assessments of well‐being as part of technology implementation are proposed as a future direction for examining the wellness impact of technology on anesthesiologists.